Humanistic Nursing Services: A Perspective on Improving Nursing Care - Suprajitno, Suprajitno; Mugianti, Sri (Health Access Journal, 2025)
Humanistic nursing is a service provided by nurses to patients by involving the patient's participation in meeting bio-psycho-socio-spiritual needs to restore health. Writing is a perspective that strengthens the importance of humanistic nursing for nurses and nursing students. The method used is a literature review sourced from nursing theory, organizational writings, expert writings, and related articles. The results of the search obtained two theories of humanistic nursing. Humanistic nursing requires two strong foundations, namely a humanistic attitude and communication skills. Humanistic nursing needs to be trained since being a nursing student.